Metacognition in multisensory perception - Deroy, O; Spence, C; Noppeney, U (Cell Press, 2016)
Metacognition - the ability to monitor one's own decisions and representations, their accuracy and uncertainty - is considered a hallmark of intelligent behavior. Little is known about metacognition in our natural multisensory environment. To form a coherent percept, the brain should integrate signals from a common cause but segregate those from independent causes. Multisensory perception thus relies on inferring the world's causal structure, raising new challenges for metacognition. We discuss the extent to which observers can monitor their uncertainties not only about their final integrated percept but also about the individual sensory signals and the world's causal structure. The latter causal metacognition highlights fundamental links between perception and other cognitive domains such as social and abstract reasoning.